Los determinantes del ahorro privado en el Perú y el papel de la política económica - Barreda, Jorge (2000)
The research is about the behavior of private saving in the Peruvian economy and its fundamentals in last half century. On the neoclassical model of growth and some assumptions about the parameters, the authors find that the domestic saving rate that maximizes the intertemporal consumption fluctuates between 28% y 33% of GDP. lt means, more than 10 points of GDP than the 17,4% registered in 1996. The research also finds theoretical and practical foundations for an active fiscal policy oriented to increase the public saving rate. ln addition, the authors estimate an empirical time series model of the actual behavior of the private savings that fulfills hard statistical tests. Finally, using the statistical model, under some growth and external savings scenarios, the domestic saving rate will be in the optimal range in six or seven years (2003).